Prognostic Factors for Checkpoint Inhibitor Based Immunotherapy: An Update With New Evidences - Yan, Xinyu; Zhang, Shouyue; Deng, Yun; Wang, Peiqi; Hou, Qianqian; Xu, Heng (Frontiers in Pharmacology, 2018)
Checkpoint inhibitor (CPI) based immunotherapy (i.e., anit-CTLA-4/PD-1/PD-L1 antibodies) can effectively prolong overall survival of patients across several cancer types at the advanced stage. However, only part of patients experience objective responses from such treatments, illustrating large individual differences in terms of both efficacy and adverse drug reactions. Through the observation on a series of CPI based clinical trials in independent patient cohorts, associations of multiple clinical and molecular characteristics with CPI response rate have been determined, including microenvironment, genomic alterations of the cancer cells, and even gut microbiota. A broad interest has been drawn to the question whether and how these prognostic factors can be used as biomarkers for optimal usage of CPIs in precision immunotherapy. Therefore, we reviewed the candidate prognostic factors identified by multiple trials and the experimental investigations, especially those reported in the recent two years, and described the possibilities and problems of them in routine clinical usage of cancer treatment as biomarkers.